Modeling and simulation of electro-hydraulic telescopic elevator system controlled by programmable logic controller - Istabraq Hassan Abed Al-Had; Farag Mahel Mohammed; Jamal A.-K. Mohammed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Traditional hydraulic cylinders are widely used in industry as load lifting tools. There is difficulty in employing these cylinders in narrow installation space like building elevators as well as they require a long working stroke, so solving this problem requires using the telescopic hydraulic cylinder instead. This cylinder is a unique hydraulic cylinder design that uses a sequence of decreasing diameters to create a long operating stroke in a compact-retracted form. In this work, the Auto Station software is used to build a telescopic hydraulic cylinder model that includes hydraulic elements such as double-acting hydraulic telescopic cylinders, pump, valves, pipeline, and filter, as well as electrical parts such as programmable logic controller (PLC), push-bottoms, and position sensors. The proposed model is operated by a PLC controller and has three floors with an overall height of around 300 cm for lifting a 100 kg payload. The accuracy and validity of this model in lifting big weights were demonstrated by the analytical findings of characteristic curves for cylinder position and velocity. This model can be used a basic reference to analyze and construct hydraulic cylinders with any number of stages. The findings of simulations reveal that a quick change in pressure due to phase change causes multi-phase vibration.